The Seven Habits of the Good Life: How the Biblical Virtues Free Us from the Seven Deadly Sins - Kaplan, Kalman J.; Schwartz, Matthew B. (Rowman & Littlefield Publishers, 2006)
In The Seven Habits of the Good Life, the authors highlight seven biblical gifts_self-esteem, wisdom, righteousness, love, healthy appetite, prudence, and purpose_and present each one as an alternative to one of the seven deadly sins. Each gift gives readers a chance to enrich their lives by integrating concern for themselves with a healthy concern for others rather than punishing themselves for bad behavior. Incorporating clinical case studies, the voices of real people, and biblical stories, this book shows how the wisdom of the scriptures can provide us concrete ways of redefining difficult situations and approaching life in a way that strives for fullness, harmony, and balance.